Sonate, op. 2 no. 2 / L. van Beethoven ; analysées par Georges Sporck - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Sporck, Georges, 1870-1943:::Contributor:::::::::::: (Édition analytique des classiques, E. Ploix, Editeur; Paris, 2022)
Edition of the Piano Sonata no. 2 in A major, op. 2, no. 2, issued in the "Edition analytique des classiques" edited by George Sporck; with a series title page listing the 32 individual piano sonatas opp. 2-111. Includes preface "aux professeurs et aux éleves," a historical introduction by H.C. Houssaye, fingerings, and pedal markings, and analysis of form in the margins, in French, with English and German translations at back.